Mesoporous Bioactive Glass Nanoparticles Promote Odontogenesis and Neutralize Pathophysiological Acidic pH - Huang, Wenyan; Yang, Jingjing; Feng, Qiong; Shu, Yan; Liu, Cong; Zeng, Shihan; Guan, Hongbing; Ge, Lihong; Pathak, Janak L.; Zeng, Sujuan (Frontiers in Materials, 2020)
Pathophysiological acidic-pH hinders the dental biomaterial-based pulp-dentin regeneration. Bioactive glass (BG) synthesized by sol-gel methods had shown odontogenic and pulp regeneration potential. However, the pathophysiological acidic-pH neutralizing potential of BG has not been tested yet. In this study, we aimed to design mesoporous BG-nanoparticles by a well-established sol-gel method and test its odontogenic and acidic-pH neutralizing potential. BG-nanoparticles were synthesized and further characterized by SEM, EDS, XRD, and FTIR. Mono-dispersed and spherical mesoporous BG-nanoparticles with size 300–500 nm were successfully fabricated. Effect of BG ionic extraction in DMEM with 0.1–2.5 g/L BG concentrations on proliferation and odontogenic differentiation of stem cells from human exfoliated deciduous teeth (SHED) was analyzed. All the BG ionic extractions did not affect SHEDs proliferation at early time points (day 1 and 3). BG ionic extraction 0.5 g/L robustly enhanced odontogenic differentiation of SHEDs, as shown by the expression pattern of ALP, Col1, DSPP, and matrix mineralization results. The chemical composition of the BG ionic extraction-induced mineralized matrix resembled natural dentin. BG-nanoparticles/alginate paste neutralized the butyric acid solution (pH 5.4) and buffered within pH 8.3 for a month. Our findings showed the odontogenic and pathophysiological acidic-pH neutralizing potential of BG-nanoparticles, indicating its possible application in pulp-dentin regeneration under pathophysiologically challenged acidic environment.